A regioselective and convenient one-pot multicomponent synthesis of 9-amino-3, 5-diaryl-4, 9-dihydro-5H-[1, 2, 4]triazolo[5, 1-c][1, 2, 4]triazepine-8-thiol. Issue 11 (3rd June 2017) - Moustafa, Amr Hassan; Amer, Amer Anwar
ABSTRACT: An efficient and environment-friendly procedure for the synthesis of a new series of nitrogen bridge-head [1, 2, 4]triazolo[5, 1- c ][1, 2, 4]triazepine derivatives through one-pot three-component reaction of polyfunctional triazole with aromatic aldehydes and acetophenone derivatives using alcoholic sodium hydroxide solution. The same new products were prepared in classical route through reaction of triazole with the corresponding chalcones under the same conditions. GRAPHICAL ABSTRACT: